Motivations for allyship with mental health consumer movements. Issue 4 (2nd October 2021) - Moss, Cameron; Warner, Terri; Happell, Brenda; Scholz, Brett
ABSTRACT: People working within mental health organisations or systems but not in dedicated lived experience roles might still make contributions as allies to mental health consumer movements. The current study explores the motivations of such allies, specifically in relation to collaborations with consumers and targeting systemic change when providing support. Semi-structured interviews were held with 11 participants identified as allies to consumer movements. Interview data were examined using a synthesis of inductive and deductive thematic analysis. The findings indicated the motivations of allies could be understood in relation to three themes: social justice values, witnessing support for consumers, and perceptions of valuable consumer contributions. Participants discussed no single primary motive, instead reporting a combination. The motives identified have implications for allies' involvement in and mobilisation with consumer movements. Allies using their power and influence to make opportunities for consumer empowerment might improve mental health policy, services, and academia.